Prevalência do papilomavírus humano e associação dos polimorfismos GST na infecção viral - Bortolli, Ana Paula Reolon (2021)
The infection caused by Human Papillomavirus (HPV) is common in sexually active women and can cause intraepithelial lesions that can progress to cervical cancer (CC). The objective of the study was to determine the prevalence of HPV and to investigate whether there is a relationship between polymorphisms, GSTT1 and GSTM1, with susceptibility to viral infection and associated risk factors in a group of women. The largest survey involved 324 women, who were recruited in services of the network accredited to the Unified Health System (Sistema Único de Saúde). The participants were interviewed and through the collection of biological material from the endocervical brushes of the Pap smear, the prevalence of the virus and the characterization of GSTM1 and GSTT1 polymorphisms were determined. For molecular detection of HPV, primers from the coding region of the virus L1 gene were used, MY09 (5'-CGTCCMAARGGAWACTGATC-3') and MY11 (5'GCMCAGGGWCATAAYAATGG-3'), obtaining a 450 bp fragment. The Multiplex PCR method was used to determine the GSTM1 and GSTT1 genetic polymorphisms. The primer pairs used were: Forward 5'GAACTCCCTGAAAAGCTAAAGC-3’ and reverse 5'-GTTGGGCTCAAATA TACGGTGG-3’ and Forward 5'-TTCCTTACTGGTCCTCACATCTC-3’ and reverse 5'-TCACCGGATCATGGCCAGCA-3'. The first produces an amplicon of 219bp and the second of 459bp, respectively, for the GSTM1 and GSTT1 genes. HPV was detected in 22 (6.8%) women and of these seven (58.3%) had cytopathological alterations. The multivariate model pointed out as possible associations with the presence of HPV the current cervical changes that increase almost 33 times the chance of the presence of HPV (ORadj: 32.688; CI 95% 8.508-125.589; p<0.001), recent vaginal infection (ORadj: 2.773; 95% CI 1.048-7.341; p<0.040) and belong to races other than white (ORadj: 3.058; 95% CI 1.056-8.857; p<0.039). A case-control study was designed from the initial sample to verify the relationship between GSTM1 and GSTT1 with viral infection. The number of cases (21) and controls (84) were matched by age. In the study, the prevalence of HPV was 6.8%, and these 58.3% had cytopathological changes. Smoking has been shown to increase the chance of viral infection up to 3.6 times. Still, it revealed in an unprecedented way that the GSTT1 null allele was a protective factor, that is, because women who have a deletion are less susceptible to HPV infection.